Effects of Surface-Modified Graphite on Tribological Properties and Thermal Conductivity of Fabric Self-Lubricating Liner - Hu, Zhanqi; Wang, Zhanshan; Chen, Jigang; Fan, Bingli; Qi, Xiaowen; Ma, Jian; Gu, Dapeng; Yang, Yulin; Song, Laizhou (Asian Journal of Chemistry, 2014)
The surface-modified graphite powder was used as high thermal conductivity filler to fabricate the woven structure fabric self-lubricating liner. Thermal conductivity and tribological properties of the fabric self-lubricating liners filled with graphite were investigated using KY-DRX-RW tester and MMU-5G tribological tester, respectively. Results showed that the thermal conductivity of the liner filled with 10 wt. % graphite was improved by about 15 % under normal temperature comparing with liner without graphite. By affecting the viscosity of the tribofilm, the graphite improved the wear resistance of the fabric liner filled with graphite and showed opposite effect on the antifriction property. In particular, fabric self-lubricating liner filled with 10 wt. % graphite showed relatively high thermal conductivity, significant low wear loss, slightly increased but steady friction coefficient and integrated weave structure.